Observation of B+→J/[psi]3π+2π− and B+→[psi](2S)π+π+π− decays - Aaij, Roel; D'Argent, Philippe; Bachmann, Sebastian; Braun, Svende; Britsch, Markward; Comerma-Montells, Albert; De Cian, Michel; Esen, Sevda; Gerick, David; Gersabeck, Evelina; Han, Xiaoxue; Hansmann-Menzemer, Stephanie; et al. (The European physical journal. C, Particles and fields, 2017)
The decays B+→J/ψ3π+2π−B+→J/ψ3π+2π−{{\mathrm {B}} ^+} \rightarrow {{\mathrm {J}/\uppsi }} 3{{\uppi } ^+} 2{{\uppi } ^-} and B+→ψ(2S)π+π+π−B+→ψ(2S)π+π+π−{{\mathrm {B}} ^+} \rightarrow {\uppsi {(2\mathrm {S})}} {{\uppi } ^+} {{\uppi } ^+} {{\uppi } ^-} are observed for the first time using a data sample corresponding to an integrated luminosity of 3.0 fb−1−1^{-1}, collected by the LHCb experiment in proton-proton collisions at the centre-of-mass energies of 7 and 8TeVTeV\mathrm {\,TeV}. The branching fractions relative to that of B+→ψ(2S)K+B+→ψ(2S)K+{{\mathrm {B}} ^+} \rightarrow {\uppsi {(2\mathrm {S})}} {{\mathrm {K}} ^+} are measured to be B(B+→J/ψ3π+2π−)B(B+→ψ(2S)K+)=B(B+→ψ(2S)π+π+π−)B(B+→ψ(2S)K+)=(1.88±0.17±0.09)×10−2,(3.04±0.50±0.26)×10−2,B(B+→J/ψ3π+2π−)B(B+→ψ(2S)K+)=(1.88±0.17±0.09)×10−2,B(B+→ψ(2S)π+π+π−)B(B+→ψ(2S)K+)=(3.04±0.50±0.26)×10−2,\begin{aligned} \dfrac{{\mathcal {B}} ( {{\mathrm {B}} ^+} \rightarrow {{\mathrm {J}/\uppsi }} 3{{\uppi } ^+} 2{{\uppi } ^-} )}{{\mathcal {B}} ( {{\mathrm {B}} ^+} \rightarrow {\uppsi {(2\mathrm {S})}} {{\mathrm {K}} ^+} )}= & {} ( 1.88\!\pm \! 0.17\!\pm \! 0.09)\!\times \! 10^{-2}, \\ \dfrac{{\mathcal {B}} ( {{\mathrm {B}} ^+} \rightarrow {\uppsi {(2\mathrm {S})}} {{\uppi } ^+} {{\uppi } ^+} {{\uppi } ^-} )}{{\mathcal {B}} ( {{\mathrm {B}} ^+} \rightarrow {\uppsi {(2\mathrm {S})}} {{\mathrm {K}} ^+} )}= & {} ( 3.04\!\pm \!0.50\!\pm \!0.26)\!\times \! 10^{-2}, \end{aligned}where the first uncertainties are statistical and the second are systematic.
Im Titel sind die Plus- und Minus-Zeichen hochgestellt
Im Titel werden "psi" und "pi" als griechische Buchstaben dargestellt
LHCb Collaboration: R. Aaij, P. d’Argent, S. Bachmann, S. Braun, M. Britsch, A. Comerma-Montells, M. De Cian, S. Esen, D.Gerick, E. Gersabeck, X.Han, S. Hansmann-Menzemer, M. Kecke, B. Khanji, M. Kolpin, K. Kreplin, B. Leverington, J. Marks, M. Meissner, D.S. Mitzel, S. Neubert, M. Neuner, T. Nikodem, A. Piucci, P. Seyfert, M. Schiller, M. Stahl, S. Stemmle, J. v. Tilburg, U. Uwer, M. Vesterinen, R. Waldi, A. Zhelezov [und weitere]
Gesehen am 30.10.2018